Quantitative Structure-Activity Relationship of 3-Thiocyanate-1H-Indoles Derived Compounds as Antileukemia by AM1, PM3, and RM1 Methods - Irvan Maulana Firdaus; Ponco Iswanto; Ahmad Fawwaz Dafaulhaq; Ahmad Ghifari Ramadhani; Maylani Permata Saputri; Heny Ekowati (Jurnal Kimia Sains dan Aplikasi, 2023)
Cancer is a disease with fatal consequences; thus, searching for innovative compounds with anticancer properties remains an active pursuit. One of the highly promising candidates is a compound derived from 3-thiocyanato-1H-indoles. However, the number of derivative compounds is currently limited. A quantitative structure and activity relationship (QSAR) study was conducted on derivate compounds 3-thiocyanato-1H-indoles to establish equations that predict the anticancer activity of more effective derivatives. This study aims to compare the effectiveness of the AM1 (Austin Model 1), PM3 (Parameterized Model 3), and RM1 (Recife Model 1) semiempirical methods, which are new techniques implemented in the Hyperchem version 8.0. Twenty experimental data were used, 16 derivatives of 3-thiocyanate-1H-indoles as regression compounds (fitting) and four derivates as test compounds. QSAR analysis was performed based on multiple linear regression calculations on 3-thiocyanate-1H-indoles derivative compounds by plotting IC50 (µM) as the dependent variable and descriptors as the independent variable. The best QSAR equation was obtained from the AM1 semiempirical calculation method with the following equation: IC50 = -1.705 + 0.511(Delta) + 0.346(Dipol) + 18.287(qC9) – 0.645(Log P) + 13.952(qC6), with n =20; r =0.814; r2 =0.662; The standard error (SE) =1.044; Fcount/Ftable =1.851; PRESS =15.219.